Joint torque and muscle velocities in the swing phase of slow and fast running - Bober, T.; Pietraszewski, B. (2001)
The aim of the paper is a comparison of torque in hip and knee joint and velocity of contraction of selected muscles acting on these joints in the swing phase in marathon running and sprinting. This investigation contributes to the problem explored by Winter (1979) and Wood (1987). Motion picture method was applied to register movement of three sprinters (velocity 7.2-8.7 m/s) and four marathoners at the second part of the distance (velocity 3.4-3.8 m/s). Using the data of Frigo and Pedotti (1978) the velocity of contraction of m. iliacus, rectus femoris and vastus lateralis was calculated. In addition the torque of hip flexion and knee extension was found. In general, greater torque in hip correlates with smaller velocity of m. iliacus contraction, and conversely smaller torque in knee goes with higher velocity of contraction of muscles acting on that joint. Positive torque of the swing in hip and knee joints is about 40% smaller in slow than in fast running with one exception of marathoner #3. Vigorous knee extension as compared to hip flexion is typical for sprinting. This is explained by higher difference in velocity of m. rectus f. and vastus l. and smaller of m. iliacus in these two kinds of running.